Opportunity in ready to eat food products market during the outbreak of Corona Virus in Bangladesh - Nayan, H.M. Afazuddin (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.